THE VISUALLY IMPAIRED STUDENTS’ LEARNING ENGLISH APPLYING TOTAL PHYSICAL RESPONSE (TPR) - Sri Wiyanah (Journal of English Language Teaching and English Linguistics, 2017)
The research aims to describe the visually impaired students’ learningEnglish using Total Physical Response (TPR). The research may contribute to thedevelopment of English learning model for the visually impaired students whoneed attention in their right to get better education and improvement in learningEnglish using Total Physical Response (TPR). The research method wasdescriptive qualitative method. The study was conducted at YaketunisYogyakarta. There were fifteen visually impaired students who becameparticipants in this research. The sources of the data were (1) visually impairedstudents as the participants of the study, (2) recorded actions (video-taped), (3)recorded interviews (audio-taped), and (4) field note.The result showed that visually impaired students had new experience inlearning English effectively, actively, stress-free and joyful. Total PhysicalResponses handled that students’ limitation in visualization to get informationthrough voice by their senses of hearing. The students practiced giving responsesof some instructions, pronunced some words and repeated the words many timesby maximizing their sense of hearing to activate their psychomotor competence.This process of learning activities supported them in developing their skill inmastering vocabulary, expression, and language command.